Peran Layanan Bimbingan dan Konseling Islam dalam Mengatasi Keadaan Stres Santri Akibat Isolasi Mandiri - Syafiq, Mohamad; Tamam, Majiddhut (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2023)
This research aims to determine the role of Islamic guidance and counseling services to overcome feelings of stress among students due to self-isolation and how Islamic guidance and counseling is implemented. The research method is qualitative, with a descriptive approach and using a case study type of research. Data collection techniques; observation, interviews and documentation. Data analysis uses comparative descriptive analysis techniques, namely by comparing the counseling service process between theory and the field. The results compared students' feelings of stress before and after receiving services at the Islamic boarding school. In conclusion, the process of Islamic guidance and counseling services at the Qomaruddin Islamic boarding school includes an orientation service called Masa Taaruf Santri Baru, placement services that are applied to extracurricular activities, and individual counseling services. As a result, there was a change in stress messages among students for the better and this was proven by the absence of students returning home during the isolation period